PRIMER REGISTRO DE THALASSIONEMA PSEUDONITZSCHIOIDES (SCHUETTE & SCHRADER) HASLE (THALASSIONEMATACEAE, BACILLARIOPHYCEAE) EN EL PACIFICO SURORIENTAL FRENTE A LA COSTA DE CHILE - Rivera, Patricio; Cruces, Fabiola; Avaria, Sergio (Gayana Botánica, 2004)
This note reports the finding of Thalassionema pseudonitzschioides (Schuette & Schrader) Hasle in samples collected in Iquique Bay (20º12’S, 70º10’W), in northern Chile. This is the first record of the species for the region. The taxon has been associated mainly with subtropical to temperate waters.